Penanaman Nilai Karakter Cinta Tanah Air Pada Siswa Di SMP PGRI 1 Buduran - Pandu Rudy Widyatama; Suhari (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
Research with a descriptive qualitative approach aims to discover the forms of instillation of the character value of love for the country in students and the role of teachers and principals in instilling the value of the character of love for their students. The research subject is students, teachers, and principals—observation methods, interviews, and documentation. The results showed that there was an instillation of the character values of love for the country in students at SMP PGRI 1 Buduran according to indicators, namely using local products; using Bahasa; respect for the culture; displaying photos of leaders, flags, and emblems, maps, drawings; appreciate heroes; singing national and regional songs; protecting the environment; respect the results of achievements; and uphold the name of the country. The teacher's role is to provide guidance and habit, which is crucial. The role of the principal is to supervise and be an example.